Insights Into the Source of Magmatic Hot-Lines: Forty Years of Geophysical Studies of the Cameroon Volcanic Line - Adams, Aubreya (Frontiers in Earth Science, 2022)
The Cameroon Volcanic Line (CVL) of west Africa poses many challenges to common models of mantle processes and volcanic system genesis. Although the CVL superficially resembles the hot-spot trace of a mantle plume, there is no evidence for age progression of initiation or cessation of volcanic activity, making the CVL one of several hot-lines observed on Earth, which exhibit asynchronous volcanism along each line. This unusual form of volcanic system, together with the complexity of the surrounding geology, which includes a Mesozoic rift, an Archean Craton, a Proterozoic mobile belt, and a major continental-scale shear zone, have fueled numerous geophysical investigations of the crust and upper mantle structure within the region. This review highlights major findings from geophysical studies, including controlled source and passive source seismic studies and gravimetric modeling, conducted in the late 20th and early 21st centuries. Potential geodynamic models for the formation of the CVL are examined and evaluated based on the body of geophysical evidence. Finally, several key outstanding questions about the structure and formation of the CVL are highlighted, potentially guiding future studies of this region.